Profissionalização docente sob a ótica da Andragogia: um estudo com professores no ensino da Administração em uma universi-dade pública na Bahia. - JESUS, Daniela Magalhães Costa de (2017)
The main objective of this study is to analyze the adherence of teacher training to the andragógico model of teacher learning, who work in the teaching of Administration in two courses at the State University of Bahia. With regard to the specific objectives: a) to identify the characteristics of the teacher training of the professional who works in the administration course; b) delimiting the competences provided for in the pedago-gical model; c) delimiting the skills provided in the andragógico model; d) measure the lack of these competences in the university teaching-administration form; e) iden-tify causes and consequences of this phenomenon. In order to understand the work theme, the theoretical foundation was made, which addresses the management of the educational service, the quality of the educational service, the characteristics of the organizations and the educational work, the process of teaching and learning, teacher competence and an andragogic learning perspective. The research is of a qualitative and quantitative nature, of the exploratory and descriptive type, carried out in two stages: a quantitative one, through a research questionnaire with 20 teachers from two campuses, and another qualitative phase, through of semi-structured inter-views. The results obtained showed that teachers adherence to the andragogic mo-del of learning, however, it is noticed that teachers act in a more intuitive than profes-sionalized way influenced by the technical character of the course of administration. The results made it possible to broaden the discussion about the precariousness of teacher professionalization and its repercussion for the teaching of Administration.